Socio-economic status and the impact of the 'Continuous Assessment and Progression System' in primary education in Myanmar. Issue 6 (17th August 2020) - Yoshida, Natsuho
ABSTRACT: This study investigated the effects of the Continuous Assessment and Progression System (CAPS) on grade repetition and dropout rates as a function of household socio-economic status (SES). Participants attended five schools in urban Myanmar and were classified into three SES groups. Results showed unequal CAPS effects: the middle SES group benefited most, with repetition and dropout rates approaching zero post-CAPS implementation. The high SES group was at ceiling pre- and post-CAPS, so was unaffected. Results were mixed for the low SES group; grade repetition was roughly halved, but high dropout rates persisted. Thus CAPS effects were mitigated in severe socio-economic circumstances.